PENINGKATAN PEMAHAMAN LITERASI KEUANGAN UNTUK GURU SMP SWASTA PAHLAWAN NASIONAL MEDAN - Siregar, Fachrul A (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
The understanding of financial literacy obtained from financial education will then enable individuals to have sufficient knowledge about how to take advantage of the investments they make. Investment choices are based on the assumption that individuals are interested in and capable of making decisions about their finances. The method used in the community service model is through lectures, tutorials and simple financial planning practices. This community service is carried out together with teachers at Medan National Pahlawn Middle School. The material provided is in the form of financial literacy and training in making financial plans to provide an understanding of managing current and future income and expenditure needs. Through this training, partners are expected to be able to plan well and correctly.